Internet-/Arduino-controlled PV automatic irrigation system for clean environment - Senpinar, A. (Springer, 2019)
In recent years, climate change and global warming has resulted in large amount of water required for irrigation. The designed system is an electronically controlled automatic irrigation system by using Arduino based on soil humidity sensors. An automatic photovoltaic (PV) pumping system consists of at least seven basic components, namely a PV array, a dc pump motor, a battery charge regulator, a water tank, soil humidity sensors, solenoid valves, and Arduino systems as the electronics control unit. Soil humidity sensors are placed in four different lines in the soil and controlled by four various solenoid valves. Water requirement of soil increases during consistent sunny days. The data received from the soil humidity sensors are compared with the reference values of an Arduino unit. When the humidity level of the soil is less than a certain reference level, the pump motor is started by opening its line solenoid valve. Thereafter, the land irrigation process begins. Each line is irrigated separately through a solenoid valve that is connected to the pump motor. Hence, the DC pump motor is controlled using the Arduino unit. In addition, the automatic irrigation system is monitored via a Web site and can be manually controlled if necessary. The designed system is implemented in laboratory conditions, and the results obtained are satisfactory.
4th International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 04-08, 2017 -- Kemer, TURKEY
Keywords: Arduino system; PV automatic pumping; Soil humidity sensors